Out for ourselves : the lives of Irish lesbians & gay men - Boyd, Clodagh; Doyle, Declan; Foley, Bill (Dublin Dublin : Dublin Lesbian and Gay Men's Collectives Women's Community Press, 1986)
Fonds Suzan Daniel (FSD)
Engels
Monografie